Evaluation of the Marine Space Utilization Program in North Kalimantan Province - Mursalin, Syahrullah; Ibrahim, Muh. Akmal; Ahmad, Badu; Muhammad, Sawedi (Newinera Publisher, 2024)
To carry out marine space utilization activities, every individual or entity operating permanently in territorial waters and jurisdiction must have a Conformity for Marine Space Utilization Activities (KKPR). Marine KKPR is a document that measures planned activities for suitability with the marine environment and seawater quality. This research aims to analyze the evaluation of marine space utilization programs in North Kalimantan Province. This research uses a descriptive qualitative approach with data collection methods, namely observation, in-depth interviews, and documentation. The informants in this research are the authorities and are directly involved in strategic management in the use of marine space in North Kalimantan Province. The results of the research show that the evaluation of the marine space utilization program in North Kalimantan Province still needs to be improved. This is because people still often ignore the legality of the business permits, they are running. Therefore, the government must continue to increase awareness regarding the importance of paying attention to business permits and also seaweed cultivation areas, so as not to disrupt shipping lanes.